Self-care after autologous bone marrow transplantation within the nursing care process - Edna Aparecida Barbosa de Castro; Angélica Mônica Andrade; Kelli Borges dos Santos; Teresa Cristina Soares; Luana Torres Esterci (Rev Rene)
This article reports a qualitative investigation, based on Dorothea Orem`s theoretical assumptions, which aimed to understand how the guidance given at discharge about the care related to bone marrow transplantation influence in self-care after discharge.  The sample was composed of seven adults from a municipality of upstate Minas Gerais, who underwent the transplantation and were discharged from hospital between October 2004 and September 2010. The data were collected in January 2011 through domiciliary visits, semi-structured interviews and observation.  Results from the thematic analysis pointed to a discussion on counseling received at discharge and the requirements for post-transplantation self-care. The self-care needs revealed by this study strengthen the importance of systematization of the nursing care, so that counseling received at discharge can effectively contribute to the patients` rehabilitation.